2012
DOI: 10.1016/j.fgb.2012.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Gliotoxin effects on fungal growth: Mechanisms and exploitation

Abstract: a b s t r a c tAlthough initially investigated for its antifungal properties, little is actually known about the effect of gliotoxin on Aspergillus fumigatus and other fungi. We have observed that exposure of A. fumigatus to exogenous gliotoxin (14 lg/ml), under gliotoxin-limited growth conditions, results in significant alteration of the expression of 27 proteins (up-and down-regulated >1.9-fold; p < 0.05) including de novo expression of Cu, Zn superoxide dismutase, up-regulated allergen Asp f3 expression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 52 publications
1
77
0
Order By: Relevance
“…Relevantly, it has been demonstrated that the A. fumigatus ⌬gliG strain does not exhibit increased sensitivity to gliotoxin or H 2 O 2 (11). Indeed, it has also been noted that gliotoxin may play a role in regulating the redox status of A. fumigatus (7,33). However, despite extensive analyses, no evidence of enhanced gliotoxin efflux was detectable following exposure of A. fumigatus to H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevantly, it has been demonstrated that the A. fumigatus ⌬gliG strain does not exhibit increased sensitivity to gliotoxin or H 2 O 2 (11). Indeed, it has also been noted that gliotoxin may play a role in regulating the redox status of A. fumigatus (7,33). However, despite extensive analyses, no evidence of enhanced gliotoxin efflux was detectable following exposure of A. fumigatus to H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Reduction and alkylation (using 5=-iodoacetamidofluorescein; 5=-IAF) of organic extracts was performed as described previously (11,12). For intracellular metabolite analysis, mycelia were lysed as described previously (7,17) prior to reduction and alkylation (11,12). Alternatively, total mycelial thiol quantitation was undertaken using aldrithiol-4 (11 mg/ml in ethanol) analysis (35).…”
Section: Methodsmentioning
confidence: 99%
“…S2) over a 4 h period. Interestingly, A. nidulans is also sensitive to exogenous GT [6], and is devoid of the gli cluster responsible for GT biosynthesis [4]. This observation shows that GT-naïve Aspergillus spp.…”
Section: In Vivo and In Vitro Methylation Of Exogenous Gt By A Nigermentioning
confidence: 90%
“…It has been revealed that the secretome of A. fumigatus can inhibit the growth of Candida albicans and Cryptococccus neoformans through the production of GT [5]. The anti-fungal properties of GT have also been observed in A. niger [6], although the mechanism of this growth inhibition is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…GSH and GSSG levels were measured as described previously by Carberry and colleagues (47), with the exception that 200 mg of mycelia was used for glutathione extraction and whole-cell lysates. Samples were diluted 1/10 for determination of GSSG levels and 1/50 for determination of GSH levels.…”
Section: Methodsmentioning
confidence: 99%